(untitled) (The Research of Medical Science Review, 2024)
Objective:- To determine the incidence pattern and severity and outcome of poisoning cases in emergency department of tertiary care hospital. Design: - prospective observational study. Materials and Methods:- All the poisoning cases due to various ingestible agents who attended Emergency department were evaluated prospectively.Results:- A total of 198 poisoning cases attended emergency department of tertiary care hospital over a study period. In this study the incidence observed was 0.7%. The overall females were 56.6% and males were 43.4%.Most poisoning occurred in the age group 15-25. Organophosphorous was the most common poisoning. Married were45.5% (n=90) and unmarried cases were 54.5 %( n=108) commonly involved in self poisoning. Intentional poisoning comprised 79.8% of all poisonings.Conclusion:- Majority of the intentional poisoning occurred in the female of younger age group and intentional poisoning was found to be most common with the mortality rate 5.6% in the poisoning reported cases. There was a significant population who suffered from the unavailability of ventilator support due to limited resources. It was observed that most of the cases were discharged after getting the primary care in the emergency department of the tertiary care hospital, but those with larger amounts of ingested poison didn’t survived even in the first two hours .